La sociología en Argentina desde la vuelta a la democracia. Vocación crítica y nuevas inserciones laborales - Blois, Juan Pedro (Nómadas. Critical Journal of Social and Juridical Science, 2009)
This article seeks to analyze the process of reorganization of the degree in Sociology at the University of Buenos Aires in the mid eighties -when the democracy was reestablished in Argentina- in connection with the growth and diversification of the non academic occupations for sociologists. It tries to account for the tensions between the discipline`s conception in which sociologists are socialized during their training at the university and the development of their professional practice outside the academy.